Dukungan Guru bagi Anak Usia Dini dalam Lingkungan Belajar Among: Studi Fenomenologi Berbasis Teori Tamansiswa - Kintania Sura Hapsari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze teacher support for early childhood in the Among learning environment based on Tamansiswa theory. The focus of the study is how teachers apply Ki Hajar Dewantara's Among System, educational trilogy, five principles, and the concept of Asah, Asih, Asuh to support holistic child development. The method used is qualitative with a phenomenological study approach. Research participants included kindergarten teachers and parents, while data collection was conducted through in-depth interviews. Data analysis was carried out through the stages of collection, reduction, presentation, and drawing conclusions, so as to obtain a comprehensive understanding of teacher practices in supporting early childhood. The results show that teachers consistently serve as role models (Ing Ngarso Sung Tulodo), guide children in the midst of learning activities (Ing Madya Mangun Karso), and provide encouragement from behind (Tut Wuri Handayani) to foster independence and self-confidence. The application of the five principles of the Among System and the concept of Asah, Asih, Asuh allows children to learn naturally, imitate positive behavior, develop cognitive and socio-emotional abilities, and foster cultural and national values. Parents reported that their children felt comfortable, enthusiastic, and developed into independent, intelligent, and character-based individuals, ready to continue their education. These findings contribute to strengthening the pedagogical framework based on local wisdom in early childhood education discourse and offer practical implications for developing national education policies that emphasize holistic and character-based learning.